Marriage in the novels of Thomas Hardy and D.H. Lawrence - Bulaila, Abdul Aziz Mohammed (1992)
This thesis is a developmental and comparative study of marriage in the novels of Thomas Hardy and D.H. Lawrence. Although this subject is frequently alluded to in recent criticism of both authors, it is rarely discussed in detail. The main interest of the study here is to show how marriage and its sub-themes of love, sex and women, as well as society's perceptions of them in the late nineteenth and early twentieth centuries, particularly in the period between 1870 and 1930, have developed in their social and psychological dimensions, and how these developments are reflected in the novels. Partly for biographical reasons Hardy and Lawrence have different motives in exploring the theme of marriage: one seeks to deconstruct it for its failure to bring fulfilment to husband and wife, the other attempts to reconstruct it anew in order to bring fulfilment to man and woman's relationship. This approach is reflected in the thesis by dividing it into three major parts: Part one is concerned with marriage in reality as it was understood by society and experienced by Hardy and Lawrence; Part two deals with marriage from two points of view; and Part three is allotted to the consideration of marital patterns.